2021
DOI: 10.1111/bcp.15073
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin poisoning: Evaluation of dose‐toxicity relationship

Abstract: W de Lange, head of the Dutch Poisons Information Center (DPIC), MD, PhD. The DPIC has no direct patient contact, but provides information to medical professionals on the treatment of poisoned patients. The medical professionals that consult the DPIC have direct clinical responsibility for the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…There are numerous reports of pregabalin use and misuse in the literature, but data on pregabalin concentrations in acute poisoning are mostly limited to case reports [4,5,[7][8][9][10][11][12]. In this work, we presented the validation of LC-MS/MS method for the quantification of pregabalin in human plasma from patients with suspected overdose of this drug.…”
Section: Discussion Of Validated Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous reports of pregabalin use and misuse in the literature, but data on pregabalin concentrations in acute poisoning are mostly limited to case reports [4,5,[7][8][9][10][11][12]. In this work, we presented the validation of LC-MS/MS method for the quantification of pregabalin in human plasma from patients with suspected overdose of this drug.…”
Section: Discussion Of Validated Methodsmentioning
confidence: 99%
“…Along with the widespread use, there has been a worrying increase in cases of PG misuse. In the last decade a number of reports of PG acute poisoning cases have been published, but data on concentrations in overdose cases are still lacking [9][10][11][12]. The National Poison Control Center (NPCC) of the Military Medical Academy in Belgrade is a reference facility in Serbia for the treatment of patients with acute poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed that ECG combined with q-SOFA score (AUC 0.808, 95%CI 0.763 ~ 0.852) had a better predictive value than PSS score (AUC 0.617, 95%CI 0.558 ~ 0.677, p<0.05). In fact, the PSS score is a widely accepted tool for predicting the prognosis for poisoning [33][34][35]. However, PSS clinical utility is limited by its complexity and subjectivity [36].…”
Section: Discussionmentioning
confidence: 99%
“…プレガバリンはγアミノ酪酸(gamma–aminobutyric acid: GABA)誘導体であり,グルタミン酸やサブスタンスPなどの興奮性神経伝達物質の放出と活性を低下させる作用がある 1)。現在,神経障害性疼痛のみならず,周術期痛,筋痙攣,レストレスレッグ症候群など,適応症の有無に関わらず広く使用されている。一方で,自傷目的による過量服用や乱用,誤用による中毒の報告が増えている 2)。重篤な副作用の発生は少なく,ほとんどの症例は支持療法のみで軽快するが,稀に昏睡や呼吸不全,不整脈を合併することがあるため注意が必要である 3)。今回我々は,人工呼吸器管理を要した正常腎機能患者のプレガバリン中毒に対してECTRを施行し,経過中の血中プレガバリン濃度を測定した2例を経験したため報告する。…”
Section: はじめにunclassified
“…プレガバリンの主な中毒症状としては,昏睡,徐脈,低血圧および人工呼吸器管理を要する呼吸不全が報告されている 3)。しかし,これらの重篤な副作用の発生頻度は5%未満であり,ほとんどの症例は24時間以内に症状が改善するため,ICUに入室することはほとんどない 7)。しかし,腎機能障害のある患者,とくに維持透析患者では昏睡などの重篤な副作用に注意が必要である。死亡例の報告もあるが,いずれも多剤併用し過量服薬した影響と考えられる 8)。今回経験した2症例の中毒症状としては,症例1では主に洞停止と意識障害,症例2では主に意識障害がみられた。症例1,2ともに多剤併用しており,とくに症例1ではカルシウム拮抗薬による中毒症状も重篤であった。…”
Section: 考  察unclassified